Usefulness of the Echo-Guided Parasternal Tunneling for the Subcutaneous Implantable Cardioverter-Defibrillator Implantation In High Body Mass Index Patient - Sasaki, Shingo; Nishizaki, Kimitaka; Ishida, Yuji; Toyama, Yuichi; Yokota, Takashi; Tomita, Hirofumi (Archives of Clinical and Medical Case Reports, 2020)
Successful implantation of the subcutaneous implantable cardioverter-defibrillator (S-ICD) (EMBLEM, Boston Scientific, Marlborough, Massachusetts, USA) in highly obese patients represented by high body mass index (BMI) is extremely difficult due to inappropriate parasternal tunneling. We attempted echo-guided parasternal tunneling during S-ICD implantation for a 59-year-old high BMI patient and succeeded in placing the lead on the optimal position.